Mortality in civilian trauma patients and massive blood transfusion treated with high vs low plasma: red blood cell ratio. Systematic review and meta-analysis. Issue 3 (July 2020) - Oliveros Rodríguez, Henry; Ríos, Fernando; Rubio, Cristhian; Arsanios, Daniel Martin; Herazo, Andrés Felipe; Beltrán, Luis Mateo; García, Paloma; Cifuentes, Annie; Muñoz, Juliana; Polanía, Javier
Abstract : Supplemental Digital Content is available in the text Abstract: Introduction: Massive bleeding in civilian trauma patients leads to dilutional coagulopathy. Transfusion with high plasma:red blood cell (RBC) ratio has been effective in reducing mortality in war trauma patients. However, in civilian trauma the evidence is controversial. Objective: To assess the impact on mortality of high vs low plasma:RBC ratio transfusion, in civilian trauma patients with massive bleeding. Methods: A systematic review and meta-analysis, including observational studies and clinical trials, was conducted. Databases were systemically searched for relevant studies between January 2007 and June 2019. The main outcome was early (24-hours) and late (30-day) mortality. Fixed and random effects models were used. Results: Out of 1295 studies identified, 33 were selected: 2 clinical trials and 31 observational studies. The analysis of observational trials showed both decreased early mortality (odds ratio [OR] 0.67; 95% confidence interval [CI], 0.60–0.75) and late mortality (OR 0.79; 95% CI, 0.71–0.87) with the use of high plasma:RBC ratio transfusion, but there were no differences when clinical trials were evaluated (OR 0.89; 95% CI, 0.64–1.26). The exclusion of patients who died within the first 24 hours was a source of heterogeneity. The Injury Severity Score (ISS) altered the association between high plasma:RBC ratio and mortality, with a reduced protective effect when the ISS was high. Conclusion: The use of high vs low plasma:RBC ratio transfusion, in patients with massive bleeding due to civil trauma, has a protective effect on early and late mortality in observational studies. The exclusion of patients who died within the first 24 hours was a source of heterogeneity. Resumen: Introducción: El sangrado masivo en los pacientes con trauma civil propicia el desarrollo de coagulopatía dilucional. La transfusión de plasma y glóbulos rojos con una relación alta ha sido efectiva para disminuir la mortalidad en pacientes con trauma de guerra; sin embargo, su evidencia en trauma civil es controversial. Objetivo: Evaluar el efecto sobre la mortalidad de la transfusión de plasma: glóbulos rojos con relación alta (TPGR-RA) versus baja, en pacientes con sangrado masivo por trauma civil. Métodos: Se realizó una revisión sistemática y metaanálisis de estudios observacionales y experimentos clínicos publicados en el periodo de enero de 2007 a junio de 2019. El desenlace principal fue mortalidad temprana (24 horas) y tardía (30 días), utilizando el modelo de efectos fijos y aleatorios. Resultados: De 1.295 estudios identificados se incluyeron 33: dos experimentos clínicos y 31 estudios observacionales. El uso de TPGR-RA mostró una disminución de la mortalidad temprana (OR 0, 67; IC 95 %, 0, 60–0, 75) y tardía (OR 0, 79; IC 95 %, 0, 71–0, 87) cuando se analizaron los estudios observacionales, pero no hubo diferencias cuando se evaluaron los experimentos clínicos (OR 0, 89; IC 95 %, 0, 64–1, 26). La exclusión de pacientes que fallecieron en las primeras 24 horas fue una fuente de heterogeneidad. La gravedad del trauma, ISS (por las iniciales en inglés de injury severity score ) modificó la asociación entre la TPGR-RA y mortalidad, siendo menor el efecto protector cuando el ISS era alto. Conclusiones: El uso de TPGR-RA en pacientes con trauma civil y transfusión masiva (TM) tiene efecto protector sobre la mortalidad en los estudios observacionales. La exclusión de pacientes fallecidos en las primeras 24 horas fue causa de heterogeneidad.